Implementasi Navigation Meshes pada Aplikasi Navigasi Augmented Reality Berbasis Android - Rinto Herlambang Apriliyanto; Sri Wulandari (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Augmented Reality is a technology that combines two-dimensional or three-dimensional virtual objects into a real environment and projects them in real time. Navigation Meshes is a 2D polygon pathfinding technology used to automatically find paths by determining which areas are allowed or not allowed for a designated agent (unit) to pass through. . Navigation Meshes (NavMesh) has become a popular concept often used in 3D game shortest pathfinding problems, as most 3D environments use polygon structures. Navigation Meshes is indeed popularly used in games, specifically applied to NPCs and players to navigate through designated areas. But what if this NavMesh is applied in a real environment using Augmented Reality technology. In this research, the author will implement NavMesh in an Android-based Augmented Reality navigation application for smartphones to help users navigate and find rooms on the first floor of the front building of the Universitas Teknologi Yogyakarta. In designing this application, the author uses the MDLC method, which consists of concept, design, material collection, creation, testing, and distribution.